PENGARUH PERNAFASAN PURSED-LIP SEBELUM LATIHAN FISIK TERHADAP KUALITAS HIDUP PASIEN PENYAKIT PARU OBSTRUKTIF KRONIS (PPOK) DI RUMAH SAKIT PANTIRAPIH YOGYAKARTA - Scholastica Fina Aryu Puspasari (MEDIA ILMU KESEHATAN, 2016)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a progressive lung illness with the main complaints of breathlessness and decreased activitiestolerance, which consequentially worsen the quality of life (QoL). COPD management aims to improve the QoLby means of rehabilitation programs. Objective: The study focused on determining the impact of physical activity(6-Minute Walk Test/6-MWT)and the combination of Pursed-Lip Breathing (PLB) before 6-MWTon COPD patients’QoL. Methods: This study occupieda quasi-experimentaldesign, which involved70 respondents,divided into 3 groups, i.e 2 intervention groups (30 respondents each) and one control group (10 respondents). Results:The majority of respondents were male (71%), aged 60-74 (56%), had normalBMI (48%), and were former smokers (59%).After 6 weeks of intervention, meaningful differences were found in the QoLbefore and after the intervention in bothgroups:6-MWT(p=0.000) and combined (p=0.000). The ordinal logistic regression test resultedthe combined intervention hadstronger effect on the quality of life (p=0.000, 47.1% contribution)than 6-MWT (p=0.012, 35.8% contribution). Respondents’ characteristics that impacted on the quality of life were smoking history and period of CPOD (p<0.05, OR: 11,376; OR: 49,75, respectively). Conclusion:It can be concluded that PLB before 6-MWT is an effective training to improve QoL of people with COPD. Keywords: Pursed-lip breathing; QoL;COPD